Managerial Insights On The Politics Of Trade Policy And Economic Development:: The Case Of Madagascar - Sadrieh, Farid (Journal of Comparative International Management, 2012)
This paper examines the challenges faced by Madagascar, and its apparel and textile sector in particular, in light of its recent suspension from the African Growth and Opportunity Act (AGOA) eligible countries, thereby ending duty free access of its products to the US. The paper provides a thorough analysis of the historic development of Madagascar‘s apparel and textile industry in the context of its creation of special economic zones or “Zones Franches” and examines other threats to its textile sector. The paper analyzes the short- as well as long-term prospects of the Zones Franches experiment, on which much hope for the development of Madagascar had been pinned and provides managerial recommendations and directions for future research.